Research Status of the Sculptural Art of the Yungang Grottoes (Mongolian Journal of Arts and Culture, 2025)
Stone art is a distinct genre of visual art that holds a profound place in the cultural and artistic history of humanity, characterized by its unique artistic and aesthetic value. On the territory of Mongolia, the arts of the Xiongnu, Xianbei, Turkic, and Mongol Empire periods flourished, creating valuable cultural heritage. Among these, the Buddhist stone sculptures of the Yungang Grottoes (an UNESCO World Heritage Site) represent an exceptionally significant subject of study. This complex dates back to the Xianbei period, boasting a history of over 1,500 years and encompassing more than 51,000 Buddhist statues, making it one of the world’s classical heritage sites. To uncover its mysteries and understand the profound meanings that reflect the philosophical and religious spirituality as well as the social structure of its time, research integrates scientific methods from multiple disciplines such as archaeology, iconography, and iconology. Scientific evaluations conducted based on these methodologies confirm that this magnificent work holds an irreplaceable position within Mongolia’s cultural treasury. They demonstrate not only its enduring artistic value but also its profound significance in the history of global cultural heritage and monumental art.Юньган агуйн уран баримлын тухай сурвалж, судалгааны тоймХураангуй: Чулуун урлаг нь хүн төрөлхтний соёл, урлагийн түүхэнд гүн ул мөртэй, уран сайхны шийдлийн үнэ цэнээрээ онцгой байр суурь эзэлдэг дүрслэх урлагийн нэг төрөл билээ. Монголын нутагт Хүннү, Сяньби, Түрэг, Эзэнт гүрний үеийн урлагууд хөгжиж, соёлын үнэт өвийг бүтээсэн. Тэдгээрийн дотор Юньган агуй (UNESCO-ийн Дэлхийн өв)-н бурхдын чулуун баримал нь маш чухал судлагдахуун билээ. Энэхүү цогцолбор нь Сяньбийн үед хамрагдах бөгөөд 1500 гаруй жилийн түүхтэй, 51,000 гаруй ширхэг бурхдын хөрөг барималтай дэлхийн сонгодог дурсгалуудын нэг юм. Түүний нууцыг нээж, тухайн үеийн философи, шашны сүнслэг ертөнц, нийгмийн бүтцийг илтгэх гүн утгыг ойлгохын тулд судалгаа нь археологи, иконографи, иконологи гэх зэрэг олон салбарын шинжлэх ухааны аргыг нэгтгэн ашигладаг. Эдгээр арга зүйн дагуу хийсэн шинжлэх ухааны үнэлгээ нь энэхүү гайхамшигт бүтээл монголын соёлын алтан сан хөмрөгт байх ёстой хосгүй өвийн байр суурийг баталж, энэ нь зөвхөн уран дүрслэлийн арилшгүй үнэ цэн төдийгүй, дэлхийн соёлын өв, уран баримлын түүхэнд нэн ач холбогдолтой гэдгийг харуулж байна.Түлхүүр үгс: Юньган агуй, уран баримал, сурвалж бичиг, судлагдсан байдал